Everolimus-Eluting Biodegradable Abluminal Coating Stent versus Durable Conformal Coating Stent: Termination of the Inflammatory Response Associated with Neointimal Healing in a Porcine Coronary Model - Masayuki Mori; Kenji Sakata; Junichiro Yokawa; Chiaki Nakanishi; Kota Murai; Hirofumi Okada; Masaya Shimojima; Shohei Yoshida; Kazuaki Yoshioka; Yoh Takuwa; Kenshi Hayashi; Masakazu Yamagishi; et al. (Journal of Interventional Cardiology)
Objectives. We evaluated the effect of the different carrier systems on early vascular response through histological analysis and scanning electron microscopy using a porcine model. Background. Although Synergy™ and Promus PREMIER™ share an identical stent material and drug elution (everolimus), they use different drug carrier systems: biodegradable abluminal coating polymer or durable conformal coating polymer, respectively. However, data regarding the impact of the different coating systems on vessel healing are currently limited. Methods. Twelve Synergy™ and Promus PREMIER™ were implanted in 12 swine. Histopathological analysis of the stented segments was performed on the 2nd and 14th days after implantation. Morphometric analysis of the inflammation and intimal fibrin content was also performed. Results. On the 2nd day, neointimal thickness, percentage of neointimal area, and inflammatory and intimal fibrin content scores were not significantly different between the two groups. On the 14th day, the inflammatory and intimal fibrin content scores were significantly lower in Synergy™ versus those observed in Promus PREMIER™. In Synergy™, smooth muscle cells were found and the neointimal layers were smooth. In contrast, inflammatory cells were observed surrounding the struts of Promus PREMIER™. Conclusions. These results demonstrate that termination of reactive inflammation is accelerated after abluminal coating stent versus implantation of conformal coating stent.